Strategi Peningkatan Tata Kelola Sistem Resi Gudang di Kabupaten Lombok Barat - Ni Made Wirastika Sari; Muhammad Zubair; Anwar Anwar; Bambang Dipokusumo (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2021)
Warehouse receipt system (SRG) is a solution prepared by the government to overcome the financing constraints faced by farmers in obtaining financing or capital assistance. However, this program not widely used by farmer. The aimed of this research was to recommend strategies for improving SRG governance in West Lombok Regency. This research was conducted in West Lombok Regency with the consideration that there is a warehouse managed by PT Pertani (Persero) which is registered as an institution in the Warehouse Receipt System. This study uses secondary data and primary data. Secondary data were obtained from literature studies. Meanwhile, primary data obtained from direct observation, in-depth interviews and by using a questionnaire with experts. The data in this study were analyzed using descriptive analysis and pairwise comparison with the Analytic Hierarchy Process (AHP). The results of this study indicate that to improve SRG governance in West Lombok Regency, the government must focus on recruiting warehouse managers who are professional and have strong entrepreneurial characteristics.